2020
DOI: 10.1155/2020/8850653
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Acupuncture Therapy in Modulating the Plasticity of Neurodegenerative Disease and Depression: Do MicroRNA and Neurotrophin BDNF Shed Light on the Underlying Mechanism?

Abstract: As the global population ages, the incidence of neurodegenerative diseases has risen. Furthermore, it has been suggested that depression, especially in elderly people, may also be an indication of latent neurodegeneration. Stroke, Alzheimer’s disease (AD), and Parkinson’s disease (PD) are usually accompanied by depression. The urgent challenge is further enforced by psychiatric comorbid conditions, particularly the feeling of despair in these patients. Fortunately, as our understanding of the neurobiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 127 publications
(177 reference statements)
0
12
0
1
Order By: Relevance
“…The precise physiological mechanisms of acupuncture in the treatment of depression are still unknown. Previous studies have shown that acupuncture can modulate neurogenesis and synaptogenesis [36], regulate neuroendocrine function [7], attenuate neuroinflammation and neuronal apoptosis [37, 38], and regulate the expression of neurotrophic factors and their receptors [39, 40] in the central nervous system. In recent years, the effect of acupuncture on central system inflammation and its underlying mechanism have attracted much attention.…”
Section: Discussionmentioning
confidence: 99%
“…The precise physiological mechanisms of acupuncture in the treatment of depression are still unknown. Previous studies have shown that acupuncture can modulate neurogenesis and synaptogenesis [36], regulate neuroendocrine function [7], attenuate neuroinflammation and neuronal apoptosis [37, 38], and regulate the expression of neurotrophic factors and their receptors [39, 40] in the central nervous system. In recent years, the effect of acupuncture on central system inflammation and its underlying mechanism have attracted much attention.…”
Section: Discussionmentioning
confidence: 99%
“…Bei neurokognitiven Störungen, wie z. B. Demenz, scheint Akupunktur u. a. über eine Wirkung auf die Neuroplastizität via BDNF einen positiven Einfluss auszuüben [112,113,114,115].…”
Section: Wirkweise Von Akupunktur Im Psychiatrischen Kontextunclassified
“…Research suggests that many microRNAs (miRNAs) participate in the regulatory effect of acupuncture on ischaemic stroke, spinal cord injury, depression, and other conditions [ 8 11 ]. However, the effect of EA on miRNA-dependent modulators in neuropathic pain is largely undefined [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some data suggest that BDNF is connected with the regulatory process by which EA relieves neuropathic pain [ 16 ]. Furthermore, as a potential target gene, BDNF is negatively regulated by a variety of miRNAs such as miR-30a, miR-206, and miR-1B [ 13 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation